2008
DOI: 10.1590/s0100-879x2008001200001
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced neuroinflammation: mechanisms and new pharmacological targets

Abstract: Stress is triggered by numerous unexpected environmental, social or pathological stimuli occurring during the life of animals, including humans, which determine changes in all of their systems. Although acute stress is essential for survival, chronic, longlasting stress can be detrimental. In this review, we present data supporting the hypothesis that stress-related events are characterized by modifications of oxidative/nitrosative pathways in the brain in response to the activation of inflammatory mediators. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
101
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(109 citation statements)
references
References 54 publications
5
101
0
3
Order By: Relevance
“…However, the etiology of chronic stress remains still unclear. Studies in patients with CFS have revealed alterations of the hypothalamic-pituitary-adrenal (HPA) axis [1,27] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the etiology of chronic stress remains still unclear. Studies in patients with CFS have revealed alterations of the hypothalamic-pituitary-adrenal (HPA) axis [1,27] .…”
Section: Discussionmentioning
confidence: 99%
“…Although acute stress is necessary for survival, chronic and long-lasting stress can be detrimental [1] . Chronic stress is characterized by persistent fatigue, infection, and rheumatological and neuropsychiatric symptoms [2] , and it has affected thousands of people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stressful occasions elicit alterations in various organ systems, including gastrointestinal, cardiovascular 1 and central nervous system 2 . Stress is connected with post-traumatic stress conditions, major depression, schizophrenia and neurodegenerative diseases 1 .…”
mentioning
confidence: 99%
“…Stressful occasions elicit alterations in various organ systems, including gastrointestinal, cardiovascular 1 and central nervous system 2 . Stress is connected with post-traumatic stress conditions, major depression, schizophrenia and neurodegenerative diseases 1 . Exposure to stress stimuli steers hyperactivation of hypothalamus-pituitary adrenal axis, behavioural changes, autonomic function and changes in adrenocorticotropin hormone as well as in corticosterone 3 .…”
mentioning
confidence: 99%